Implementasi Media Audio Visual pada Mata Pelajaran PAI Materi Sholat Kelas II MI Mutiara Sunnah Bekasi - Fadila, Teti; Basuki, Danang Dwi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
Learning activities are a process of delivering teaching material carried out by teachers to students. In this global era, the world of education has implemented learning using information technology. This is a form of evaluation and development of learning so that the learning process does not tend to be monotonous or boring for students. The existence of audio-visual media is very helpful for teachers in learning activities. The existence of audio-visual media is very helpful for teachers in learning activities. When students are less involved in learning activities, what will happen is that they find it difficult to understand the material taught. Madrasah Ibtidaiyah teachers must have the ability to create interesting learning. In PAI subjects that are closely related to sharia and worship, PAI subjects, especially in prayer material, require tools as a support for students' understanding and knowledge of prayer material, to help provide good and appropriate learning because prayer material is material that has a fair board discussion. Teachers of PAI class II subjects at Madrasah Ibtidaiyah Mutiara Sunnah on prayer materials use audio-visual media as a tool to facilitate learning activities. Therefore, from the results of the application of audio-visual media almost all students like and are excited in learning activities, students feel happy because the learning process seems interesting, this causes an increase in learning evaluation results.